Influence of a smaller goal on total shot, score and shot success rate in children`s water polo games - Suga, M.; Komori, Y.; Murase, Y.; Imada, C. (Japanese Journal of Sciences in Swimming and Water Exercise, 2014)
This study aimed to clarify the influence of a smaller goal used for children's water polo games in 2010 on total shot, score and shot success rate. Data obtained from three games using standard (spring 2009) and smaller goals (summer 2010 and spring 2011) were analyzed. Results were as follows: 1) The total score for the spring 2009 game was significantly higher than the summer 2010 game (p<0.05). 2) The total shot success rate for the spring 2009 game was significantly higher than the summer 2010 (p<0.05) and spring 2011 (p<0.05) games. 3) Middle shots occurred significantly more frequently in the spring 2011 game than the summer 2010 game (p<0.05) because direct shots from outside the 5 m line were permitted by the 2011 rules. 4) Counter attack shots and goals occurred significantly more frequently in the spring 2009 game than the summer 2010 game (p<0.05). These results indicate that shooters should adapt to the smaller goal early.